Transforming Urban Education in São Paulo: Insights into a Critical-Collaborative School Project - Liberali, Fernanda (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The world is experiencing a particularly tense moment which asks for a project that goes beyond the limiting situations posed by immediate reality. This condition considers the critical immersion of individuals in their known realities and broad emersion in multiple contexts of understanding, which may broaden their horizons of perception. Vygotsky and recent followers offer us a basis for rethinking our reality in a collaborative and critical search for forms of development beyond who we are. This article brings about projects developed with schools from very poor and wealthy communities of São Paulo, where participants act together to transform their life conditions.